The effectiveness of arbuscular mycorrhizal fungal species (Funneliformis mosseae, Rhizophagus intraradices, and Claroideoglomus etunicatum) in the biocontrol of root and crown rot pathogens, Fusarium solani and Fusarium mixture in pepper - Ayşin Bilgili (PeerJ)
This study evaluated the effectiveness of arbuscular mycorrhizal fungi (AMF) species, including Funneliformis mosseae (FM), Rhizophagus intraradices (RI), Claroideoglomus etunicatum (CE), and a Mycorrhizal mix (MM) comprising these three species, on pepper plants (Capsicum annuum L.) inoculated with two isolates of Fusarium solani (48-F. solani and 18-F. solani) and two isolates of Fusarium mix (50-F. mixture and 147-F. mixture). Analysis of variance (ANOVA)-Tukey statistics revealed that the effects of AMF inoculations on morphological parameters, disease severity, root colonization, and total spore numbers in pathogen-infected plants varied significantly depending on the AMF species and pathogen group. AMF colonization significantly reduced disease severity, with disease inhibition (DI) reaching up to 58%, depending on the specific pathogen. However, there were a few instances where the application of AMF did not lead to a reduction in disease severity. Single AMF species were more effective in enhancing the growth of pathogen-treated host plants and suppressing disease compared to the mixed AMF. The mixed AMF was only more effective in balancing pathogen-induced decreases in plant nutrients (Copper (Cu), Magnesium (Mg), Zinc (Zn), and Phosphorus (P)). Among the compared mycorrhizae, C. etunicatum (CE) was the most effective in disease suppression due to its relatively more positive effects on plant root structure, increasing root fresh weight by up to 49% in the CE+pathogen plant group compared to the control group. Root colonization rates were generally higher in plants treated with both mycorrhiza and pathogens compared to plants treated with mycorrhiza alone. Overall, the curative effects of AMFs on plants following pathogen application varied concurrently with disease severity rates caused primarily by pathogens. AMFs demonstrated greater efficacy in combating 18-F. solani, which causes less severe plant disease. However, the effectiveness of AMFs was comparatively lower against 48-F. solani and 147-F. mix., which cause more severe plant disease. This indicates that the efficacy of AMFs varies depending on the specific strain of Fusarium solani, with better results observed against strains that cause less severe plant disease.